Judicial Pardon in Contemporary Criminal Verdicts: Balancing Justice, Legal Certainty, and the Utility of Law - Gregorius Widiartana; Sajjad Hussain (Islamic Research Publiser, 2025)
The authority of judges to grant judicial pardon—namely, the discretionary power to reduce or mitigate criminal sanctions—raises fundamental legal concerns in Indonesia's criminal justice system. While judicial discretion aims to humanise the law and consider individual circumstances of offenders, its unstructured and inconsistent application often undermines the core objectives of criminal punishment: justice, legal certainty, and legal utility. This article explores the main research questions: To what extent does judicial pardon align with the philosophical objectives of criminal sentencing? How does this practice affect legal certainty and the perception of justice in society? Employing a normative legal research method that draws on statutory, conceptual, and case-based approaches, this study critically analyses judicial decisions in which leniency or mitigation was granted under the banner of judicial pardon. The findings reveal that while judicial pardon is rooted in compassionate justice, its inconsistent use without clear normative guidelines leads to sentencing disparities, erodes public trust, and potentially weakens the deterrent effect of criminal law. Nonetheless, the study also finds that judicial pardon may serve rehabilitative and restorative aims when applied judiciously, particularly in cases involving vulnerable offenders or minor crimes. This research calls for a more transparent doctrinal framework and judicial standards to ensure that judicial pardons meaningfully contribute to the balance among justice, legal certainty, and the broader utility of law in criminal adjudication.